Biometric Data Sharing in Addressing Irregular Migration and Security Issues within the Bali Process Framework for Indonesia and ASEAN Member States - Masitoh Indriani; Amira Paripurna (Jember University Press, 2020)
The Bali Process Declaration on People Smuggling, Trafficking in Persons and Related Transnational Crime acknowledges the large scale and complexity of irregular migration challenges both within and outside the Asia Pacific region. As one of the efforts to decrease irregular migration in this region, the Regional Support Office of the Bali Process (RSO) was established in 2012 to support the implementation of the Bali Process. In this regard, the Bali Process led to an opportunity to develop the use of technology and biometrics data sharing in migration and border management. The purpose of this paper is to discuss the law and policy in addressing the issue of irregular migration in Indonesia. It also explores the development of the utilization of technology and biometrics in the area of migration, security and border management, as a measure in addressing the problem of irregular migration. The discussion focuses on the role and challenges of technology and biometrics data exchange in border management as one of the most important agreements on the Bali Process. This study finds that the gaps within the ASEAN member states in regulating privacy rights and data protection have caused the difficulties in sharing and exchange data/information particularly biometric data. The method used in this research is the doctrinal legal research, which is mainly referred to as library-based research.